MASALAH DISABILITAS DAN SOSIAL KEMASYARAKATAN DI MALANG RAYA - Subasno, Yohanes (Sekolah Tinggi Pastoral IPI Malang, 2016)
Attention to the issue of disability becomes more intense and widespread in Indonesia proven by a newlaw: Undang-Undang No. 8 Tahun 2016 about Disabled Persons. The Study Program on Pastoral Ministry in its vision and mission speaks about empowering of persons with special needs by encouraging inclusive life. As a lecturer of Community Based Rehabilitation and working together with Pilar Analisa Indonesia I did a survey on disability and social problems in Malang and its regency from July 22until August 5, 2016 using random sampling. Results of this survey are: (1)Family, neighbours and public view disabled persons ranging from treating them like other persons to unhuman activities like hiding them. (2)The economic conditions of disabled persons are less or poor because of their disability and limited opportunities. (3)Government programs for disabled persons cannot be felt by them. (4)The disability of disabled persons causes that they have low self-esteem and lack of confidence. (5) The availability of special facilities for disabled persons are very rarel found including public transportation accessibilities.